Unsuspected Exposure to Beryllium: Potential Implications for Sarcoidosis Diagnoses - Laczniak, Andrew N; Gross, Nathan A; Fuortes, Laurence J; Field, R. William (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Exposure to Beryllium (Be) can cause sensitization (BeS) and chronic beryllium disease (CBD) in some individuals. Even relatively low exposures may be sufficient to generate an asymptomatic, or in some cases a symptomatic, immune response. Since the clinical presentation of CBD is similar to that of sarcoidosis, it is helpful to have information on exposure to beryllium in order to reduce misdiagnosis. The purpose of this pilot study is to explore the occurrence of Be surface deposits at worksites with little or no previous reported use of commercially available Be products. The workplaces chosen for this study represent a convenience sample of businesses in eastern Iowa. One hundred thirty-six surface dust samples were collected from 27 businesses for analysis of Be. The results were then divided into categories by the amount of detected Be according to U.S. Department of Energy guidelines as described in 10 CFR 850.30 and 10 CFR 850.31. Overall, at least one of the samples at 78% of the work sites tested contained deposited Be above the analytical limit of quantitation (0.035 µg beryllium per sample). Beryllium was detected in 46% of the samples collected. Twelve percent of the samples exceeded 0.2 µg/100 cm² and 4% of the samples exceeded a Be concentration of 3 µg/100 cm². The findings from this study suggest that there may be a wider range and greater number of work environments that have the potential for Be exposure than has been documented previously. These findings could have implications for the accurate diagnosis of sarcoidosis.